2002
DOI: 10.1029/2001ja000183
|View full text |Cite
|
Sign up to set email alerts
|

A detailed study of equatorial electrojet phenomenon using Ørsted satellite observations

Abstract: Detailed analysis of the scalar magnetic field data from Ørsted satellite for quiet days from April 1999 to March 2000 has been undertaken to study the equatorial electrojet (EEJ) phenomenon. An objective technique has been adopted for the identification of the EEJ from the satellite data and estimation of the standard parameters associated with it. EEJ strength computed using the satellite data and simultaneous ground magnetic observatory data, for the Indian and American sectors, correlate very well authenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
91
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(112 citation statements)
references
References 19 publications
(34 reference statements)
17
91
4
Order By: Relevance
“…As stated earlier, the EEJ centre in Brazil was located at 21±16 km south of the dip equator (Rigoti et al, 1999). Jadhav et al (2002) described analyses of scalar magnetic field data from the low orbiting Ørsted satellite from April 1999-March 2000 and concluded that the EEJ axis (centre of EEJ) closely followed the dip equator at an altitude of 106 km but there were small departures with the local time, with the minimum at noon. They also found that in the longitude regions near 39 • E, 285 • E and 315 • E the angular deviation of EEJ axis from the dip equator was systematically larger than 0.5 • .…”
Section: Latitudinal Variations Of X Y and Z For Different Local Hoursmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated earlier, the EEJ centre in Brazil was located at 21±16 km south of the dip equator (Rigoti et al, 1999). Jadhav et al (2002) described analyses of scalar magnetic field data from the low orbiting Ørsted satellite from April 1999-March 2000 and concluded that the EEJ axis (centre of EEJ) closely followed the dip equator at an altitude of 106 km but there were small departures with the local time, with the minimum at noon. They also found that in the longitude regions near 39 • E, 285 • E and 315 • E the angular deviation of EEJ axis from the dip equator was systematically larger than 0.5 • .…”
Section: Latitudinal Variations Of X Y and Z For Different Local Hoursmentioning
confidence: 99%
“…Surprisingly they concluded that the electrojet current peaks right at the dip equator irrespective of season or longitude. They did not refer to earlier work of Jadhav et al (2002) on the same topic. One has to examine why the analyses of satellite data by different scientists do not agree with each other and why the conclusions Luhr et al (2004) are not in conformity with the ground magnetic field measurements.…”
Section: Latitudinal Variations Of X Y and Z For Different Local Hoursmentioning
confidence: 99%
“…Early satellite observations showed diverse results (Cain and Sweeney 1973;Onwumechili and Agu 1981;Langel et al 1993;Kim and King 1999;Jadhav et al 2002;Ivers et al 2003;Lühr et al 2004). More recent studies have established that the longitudinal variation of the daytime equatorial electrojet intensity is often dominated by the so-called "wave-4" pattern with four peaks and four troughs between 0°and 360°longitudes (Le Mouël et al 2006;England et al 2006;Alken and Maus 2007;.…”
Section: Eejmentioning
confidence: 99%
“…Magnetic field satellite missions like Ørsted and CHAMP can help in this respect and map out the EEJ distribution world wide (e.g. Jadhav et al, 2002;Lühr et al, 2004). Only after considering a sufficient amount of satellite data the true longitudinal variation of the EEJ has been determined for the first time by Alken and Maus (2007).…”
Section: Introductionmentioning
confidence: 99%